Enhancing Cognitive Abilities and Delaying Cognitive Decline in the Elderly through Tailored Exercise Programs - Taheri, Morteza (Health Nexus, 2023)
The study used a systematic literature review approach to evaluate the effectiveness of tailored exercise programs on cognitive abilities and decline in the elderly. Data collection involved searching databases like PubMed, PsycINFO, Scopus, and Google Scholar, along with manual searches of reference lists. Inclusion criteria focused on peer-reviewed studies with participants aged 60 and above, involving tailored exercise interventions with measurable cognitive outcomes. The article reviews evidence on the role of exercise in improving cognitive functions in the elderly. It explores theoretical models explaining the impact of exercise on cognition and evaluates different types of exercise, such as aerobic, strength training, and yoga. The article also investigates how these interventions can delay cognitive decline, addresses the quality and limitations of existing studies, and suggests future research directions. It emphasizes the need for personalized exercise programs based on individual capabilities and environmental considerations to optimize cognitive benefits.